Anakinra and canakinumab for patients with R92Q-associated autoinflammatory syndrome: a multicenter observational study from the AIDA Network. (August 2021) - Gaggiano, Carla; Rigante, Donato; Hernández-Rodríguez, José; Vitale, Antonio; Tarsia, Maria; Soriano, Alessandra; Lopalco, Giuseppe; Iannone, Florenzo; Abdel Jaber, Masen; Giacomelli, Roberto; Wiȩsik-Szewczyk, Ewa; Cattalini, Marco; et al.
Background: This study aims at describing the therapeutic outcome of patients carrying the R92Q variant in the TNFRSF1A gene treated with anakinra (ANA) or canakinumab (CAN) and identifying any factors predictive of complete response to IL-1 inhibition. Methods: Clinical data of patients treated with ANA or CAN for recurrent inflammatory attacks due to the presence of the R92Q variant were retrospectively collected and analysed. Results: Data about 20 treatment courses with IL-1 inhibitors (16 with ANA and 4 with CAN) from 19 patients were collected. Mean age at disease onset was 20.2 ± 14.8 years. In 5 cases (26%) the R92Q variant was found in a family member affected by recurrent fever. The therapeutic response was complete in 13(68%) and partial in 2 patients (11%); treatment failure was observed in 4 cases (21%). Median AIDAI decreased from 10 (interquartile range [IQR] = 28) to 0 (IQR = 1) at the 12-month follow-up visit ( p  < 0.001). Mean ESR and median CRP dropped respectively from 40.8 ± 24.8 to 9.1 ± 4.5 mm/h ( p  < 0.001) and from 3.0 (IQR = 1.9) to 0.3 (IQR = 0.3) mg/dl ( p  < 0.001) after 12 months of treatment. A steroid-sparing effect was observed from the third month of treatment ( p  < 0.01). Thirteen patients (65%) were still on treatment at the last follow-up visit (median duration of treatment 17 (IQR = 38) months). The presence of R92Q mutation in a symptomatic relative ( p  = 0.022), the relapsing remitting disease course ( p  < 0.001) and the presence of migratory erythematous skin rashes during fever attacks ( p  = 0.005) were associated with complete efficacy of IL-1 inhibitors. Conclusions: R92Q patients showed a favourable response to ANA and CAN, particularly when the mutation segregated in a family member and when a relapsing-remitting disease course or TNF-α receptor-associated periodic syndrome (TRAPS) typical skin rash were observed. In the subgroup of patients not taking advantage of IL-1 blockage different molecular mechanisms underlying the autoinflammatory picture are likely to exist.